A Trial of In-Hospital, Electronic Alerts for Acute Kidney Injury: Design and Rationale - Wilson, F. Perry (2014)
BACKGROUND: Acute Kidney Injury (AKI) is common in hospitalized patients, increases morbidity and mortality, and is under-recognized. To improve provider recognition we previously developed an electronic alert system for AKI. To test the hypothesis that this electronic AKI alert could improve patient outcome, we designed a randomized controlled trial to test the effectiveness of this alert in hospitalized patients. The study design presented several methodologic, ethical, and statistical challenges. PURPOSE: To highlight the challenges faced and the solutions employed in the design and implementation of a clinical trial to determine whether the provision of an early, electronic alert for AKI would improve outcomes in hospitalized patients. Challenges included how to randomize the delivery of the alert system, and the ethical framework for waiving informed consent. Other methodologic challenges included the selection and statistical evaluation of our study outcome, a ranked-composite of a continuous covariate (creatinine) and two dichotomous outcomes (dialysis and death), and the use of the medical record as a source of trial data. METHODS: We have designed a randomized trial to assess the effectiveness of an electronic alert system for AKI. With broad inclusion criteria, and a waiver of informed consent, we enroll and randomize virtually every patient with AKI in our hospital. RESULTS: As of March 31, 2014, we have enrolled 2373 patients of 2400 targeted. Pre-alert data demonstrated a strong association between severity of AKI and inpatient mortality with a range of 6.4% in those with mild, stage 1 AKI, to 29% among those with stage 3 AKI (p<0.001). We judged that informed consent would undermine the scientific validity of the study and present harms that are out of proportion to the very low risk intervention. CONCLUSIONS: Our study demonstrates the feasibility of designing an ethical randomized controlled trial of an early electronic alert for AKI without obtaining informed consent from individual participants. Our study outcome may serve as a model for other studies of AKI, insofar as our paradigm accounts for the effect that early death and dialysis have on assessment of AKI severity as defined by maximum achieved serum creatinine.